Baloxavir for the treatment of Influenza in allogeneic hematopoietic stem cell transplant recipients previously treated with oseltamivir. Issue 4 (10th June 2020) - Salvatore, Mirella; Laplante, Jennifer M.; Soave, Rosemary; Orfali, Nina; Plate, Markus; van Besien, Koen; St. George, Kirsten
Abstract: Background: Seasonal influenza causes significant morbidity and mortality in allogeneic stem cell transplant (SCT) recipients. In this population, influenza virus can replicate for prolonged periods, despite neuraminidase inhibitor treatment, leading to resistance and treatment failure. Baloxavir targets the influenza polymerase and may be an effective treatment option in these patients. Methods: We used baloxavir to treat five allogeneic SCT recipients that were still symptomatic and shedding influenza virus after completing one or more treatment courses of oseltamivir and characterized the viral isolates before and during treatment. Results: Two patients were infected with influenza A/H1pdm09 carrying a neuraminidase variant (H275Y) linked to oseltamivir resistance. Both these two patients were successfully treated with baloxavir. Of the three patients infected with wild‐type influenza virus, two cleared the virus after baloxavir treatment, while the third patient developed the polymerase I38T variant linked to baloxavir resistance. Conclusions: Our data suggest that baloxavir treatment can be effective in treating neuraminidase inhibitor‐resistant influenza in profoundly immunocompromised patients. Randomized clinical trials are needed to define the role of baloxavir alone and combined with oseltamivir for the treatment of influenza in SCT recipients and other immunocompromised populations.